Crowdsourcing as an innovative tool for generating new ideas. Крaудсорсинг кaк инновaционный инструмент для генерировaния новых идей (Вестник КазНУ. Серия Экономическая, 2016)
The article examines crowd sourcing as an innovative tool for generating new ideas, solving many company problems, reducing costs and increasing profitability. The article analyzes the growing influence of crowd sourcing on the present business practice and its impact on the changing the business environment. Many companies see innovation as key to their success and are using idea crowd sourcing to help their companies innovate. However, it is often difficult to motivate individuals to think practically and from management’s perspective, and to measure employees’ contributions to such systems. Crowd sourcing is based on the assumption that in society there are always talented people who are ready for free or for a symbolic fee to generate ideas, solve problems, and even conduct research in the corporate or public order, and the main motivation for them is a reward and an opportunity to see the realization of his ideas into practice.A new crowd-sourcing tool that delegates and combines idea generation and the distribution of tasks is described, which largely solves these problems and makes the process of idea generation more measurable.
Keywords: crowdsourcing; crowdfunding; crowdvoting; G-Global; crowdrecruiting; outsourcing; employees; controversy; amateurs; volunteers